Prophylaxis of infectious diseases among Polish population travelling abroad - Magda, Inga; Gazda, Dawid; Gaik, Magdalena; Uram, Ewa; Bogacz, Rafał; Osuch, Magdalena (Journal of Education, Health and Sport, 2023)
Introduction and purpose of the study: With the gradual increase in travel, new challenges are arising in the health sector, especially with regard to infectious diseases. Growing number of Poles choose countries on other continents as their holiday destination. The aim of this study was to examine the health behaviour of Poles in relation to their travel destinations within Europe, Asia and Africa. Of particular importance were pre-travel consultations, awareness of recommended and mandatory vaccinations and malaria prevention. Material and method: The study was based on an analysis of data from a specially constructed, online questionnaire. It was completed by 237 people. Pearson’s χ2 test, T-student and ANOVA were used to analyse the survey results. The processing of the data obtained, statistical calculations and graphs were performed using the R programme. Results and conclusions: Travellers to Asian or African countries were significantly more likely to seek information on the infectious diseases their travel destination was at risk of than travellers to European countries. In addition, recommended vaccinations were significantly more frequently administered prior to travelling to Africa or Asia than before travelling within Europe. No statistically significant differences were found between travellers to Asia or Africa in terms of seeking information on the infectious diseases, having a pre-travel consultation or being administered recommended vaccinations. With regards to malaria-prone regions, travellers to Africa were more than twice as likely to take antimalarial drugs than travellers to Asia. Mandatory vaccinations were significantly more common than recommended vaccinations, although despite the obligation some travellers still chose not to receive them.